The presence of genetic risk variants within PTPN2 and PTPN22 is associated with intestinal microbiota alterations in Swiss IBD cohort patients - Yilmaz, Bahtiyar (PLoS One, 2018)
BACKGROUND: Genetic risk factors, intestinal microbiota and a dysregulated immune system contribute to the pathogenesis of inflammatory bowel disease (IBD). We have previously demonstrated that dysfunction of protein tyrosine phosphatase non-receptor type 2 (PTPN2) and PTPN22 contributes to alterations of intestinal microbiota and the onset of chronic intestinal inflammation in vivo. Here, we investigated the influence of PTPN2 and PTPN22 gene variants on intestinal microbiota composition in IBD patients. METHODS: Bacterial DNA from mucosa-associated samples of 75 CD and 57 UC patients were sequenced using 16S rRNA sequencing approach. Microbial analysis, including alpha diversity, beta diversity and taxonomical analysis by comparing to PTPN2 (rs1893217) and PTPN22 (rs2476601) genotypes was performed in QIIME, the phyloseq R package and MaAsLin pipeline. RESULTS: In PTPN2 variant UC patients, we detected an increase in relative abundance of unassigned genera from Clostridiales and Lachnospiraceae families and reduction of Roseburia when compared to PTPN2 wild-type (WT) patients. Ruminoccocus was increased in PTPN22 variant UC patients. In CD patients with severe disease course, Faecalibacterium, Bilophila, Coprococcus, unclassified Erysipelotrichaeceae, unassigned genera from Clostridiales and Ruminococcaceae families were reduced and Bacteroides were increased in PTPN2 WT carriers, while Faecalibacterium, Bilophila, Coprococcus, and Erysipelotrichaeceae were reduced in PTPN22 WT patients when compared to patients with mild disease. In UC patients with severe disease, relative abundance of Lachnobacterium was reduced in PTPN2 and PTPN22 WT patients, Dorea was increased in samples from PTPN22 WT carriers and an unassigned genus from Ruminococcaceae gen. was increased in patients with PTPN2 variant genotype. CONCLUSIONS: We identified that IBD-associated genetic risk variants, disease severity and the interaction of these factors are related to significant alterations in intestinal microbiota composition of IBD patients.